Digital learning designs in physiotherapy education: a systematic review and meta-analysis - Ødegaard, Nina Bjerketveit (BMC Med Educ, 2021)
BACKGROUND: Digital learning designs have the potential to support teaching and learning within higher education. However, the research on digital learning designs within physiotherapy education is limited. This study aims to identify and investigate the effectiveness of digital learning designs in physiotherapy education. METHODS: The study was designed as a systematic review and meta-analysis of randomized and non-randomized trials. A search of eight databases on digital learning designs and technology was conducted. Study selection, methodology and quality assessment were performed independently by three reviewers. The included studies were mapped according to the types of digital interventions and studies. For similar interventions, the learning effects were calculated using meta-analyses. RESULTS: Altogether, 22 studies were included in the review (17 randomized controlled trials and five cohort studies). A blended learning design was used in 21 studies, a flipped classroom model in five and a distance learning design in one. Altogether, 10 of the 22 articles were included in meta-analyses, which showed statistically significant effects for flipped classrooms on knowledge acquisition (standardized mean difference [SMD]: 0.41; 95% confidence interval [CI]: 0.20, 0.62), for interactive websites or applications (apps) on practical skills (SMD: 1.07; 95% CI: 0.71,1.43) and for students self-produced videos on a practical skill in a cervical spine scenario (SMD: 0.49; 95% CI: 0.06, 0.93). Overall, the effects indicated that blended learning designs are equally as or more effective than traditional classroom teaching to achieve learning outcomes. Distance learning showed no significant differences compared to traditional classroom teaching. CONCLUSIONS: The current findings from physiotherapy education indicate that digital learning designs in the form of blended learning and distance learning were equally or more effective compared to traditional teaching. The meta-analyses revealed significant effects on student learning in favour of the interventions using flipped classrooms, interactive websites/apps and students self-produced videos. However, these results must be confirmed in larger controlled trials. Further, research should investigate how digital learning designs can facilitate students’ learning of practical skills and behaviour, learning retention and approaches to studying as well as references for teaching and learning in digital learning environments. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12909-020-02483-w.